Neodymium YAG laser anterior capsulotomy in congenital cataract - Öge, İhsan and Öge, Fatma (The Turkish Journal of Pediatrics, 1987)
Prior to linear extraction, the anterior capsule was opened and softening of the lens was achieved in 15 eyes of 12 cases with congenital cataract by application of the Nd: YAG laser. A lower power setting and minimal shots were used. No significant side effects were observed.